Recurrence of endometrial carcinoma presenting as vulvar lesions. Issue 1 (6th February 2019) - Rottenstreich, Misgav; Armon, Shunit; Beller, Uzi; Rosengarten, Ora; Vernea, Fiona; Reichman, Orna
Abstract : Vulvar metastasis is an unusual presentation of recurrent endometrial cancer and should be part of the differential diagnosis of vulvar lesion.